Balance between Regulatory T and Th17 Cells in Systemic Lupus Erythematosus: The Old and the New. (14th June 2012) - Alunno, Alessia; Bartoloni, Elena; Bistoni, Onelia; Nocentini, Giuseppe; Ronchetti, Simona; Caterbi, Sara; Valentini, Valentina; Riccardi, Carlo; Gerli, Roberto
Abstract : Pathogenic mechanisms underlying the development of systemic lupus erythematosus (SLE) are very complex and not yet entirely clarified. However, the pivotal role of T lymphocytes in the induction and perpetuation of aberrant immune response is well established. Among T cells, IL-17 producing T helper (Th17) cells and regulatory T (Treg) cells represent an intriguing issue to be addressed in SLE pathogenesis, since an imbalance between the two subsets has been observed in the course of the disease. Treg cells appear to be impaired and therefore unable to counteract autoreactive T lymphocytes. Conversely, Th17 cells accumulate in target organs contributing to local IL-17 production and eventually tissue damage. In this setting, targeting Treg/Th17 balance for therapeutic purposes may represent an intriguing and useful tool for SLE treatment in the next future. In this paper, the current knowledge about Treg and Th17 cells interplay in SLE will be discussed.